Analysis of awareness and confidence in learning outcomes with students' academic motivation: SEM approach - Kurniasih, Dede Dwi; Rahman ZH, Miftah Hur; Ayunisa, Dini Arifa; Mustofa, Khabib; Siswanto, Siswanto; Maryono, Maryono (Universitas Negeri Yogyakarta, 2025)
Low self-awareness and confidence hinder learning strategies, reduce academic motivation, and prevent psychology-based educational strategies from developing optimally due to limited research integrating these factors. This study examines the influence of self-awareness and self-confidence on learning achievement, mediated by academic motivation. Data from 300 high school students in Indonesia were collected using a Likert scale questionnaire, while learning achievement was measured based on the average semester score. Structural Equation Modeling (SEM) analysis showed that self-awareness had a positive and significant effect on academic motivation (Î² = 0.45, p < 0.01) and learning achievement (Î² = 0.30, p < 0.01). Similarly, self-confidence positively influenced academic motivation (Î² = 0.35, p < 0.01) and learning achievement (Î² = 0.25, p < 0.01). Academic motivation was found to mediate the relationship between self-awareness and learning achievement (indirect effect = 0.20, p < 0.01) as well as between self-confidence and learning achievement (indirect effect = 0.15, p < 0.01). The proposed SEM model demonstrated a good fit with the data (Ï‡² = 212.34, df = 149, p < 0.01; RMSEA = 0.045; CFI = 0.97; TLI = 0.96). These findings highlight the importance of self-awareness and self-confidence in enhancing learning achievement through increased academic motivation. This study contributes theoretically to understanding psychological factors affecting learning achievement and has practical implications for developing educational interventions. Future research is recommended to adopt a longitudinal design and mixed methods and explore mediator or moderator variables for more effective educational strategies.